Entrepreneur’s View on business Challenges in Disentangle Regional Capital City: Evidence from Far Western Nepal - Bhandari, Amit; Devkota, Niranjan; Paudel, Udaya Raj; Bhandari, Udbodh (Quest Journal of Management and Social Sciences, 2024)
Background: Entrepreneurship plays a vital role in economic development by driving innovation and creating employment opportunities. However, entrepreneurs in Nepal, particularly in Far Western regions like Doti, face significant challenges that may hinder both entrepreneurial growth and the overall economic development of the region. Objective: This study aims to explore the challenges faced by entrepreneurs in Doti, in starting and sustaining new ventures. It seeks to understand the key obstacles that affect business growth and provide insights for improving the entrepreneurial ecosystem in the region. Method: A convenient sampling method was used to select 280 entrepreneurs from Doti. Data were collected using a structured questionnaire, designed and administered through KOBO. A pre-test was conducted with 5% of the sample to refine the instrument. The study employed descriptive statistics to analyze the data and identify the major challenges faced by entrepreneurs. Result: The findings reveal that more than half of the respondents in Doti faced significant entrepreneurial challenges. The most prevalent issues included changes in regional capital, lack of financial resources, insufficient innovation, a limited market size, and political instability. These challenges were found to severely impact the growth and sustainability of businesses in the region. Conclusion: The study highlights the pressing need for strengthened entrepreneurial policies, increased government support, promotion of technology and innovation, and better management of business resources in Doti. Addressing these challenges is essential to fostering a conducive environment for entrepreneurship and unlocking the economic potential of Far Western Nepal. Paper Types: Research Paper Keywords: Entrepreneurship, business challenges, Economic Development, Far Western Nepal JEL Classification: L26, O18, R11